Value orientations, life transitions, and desistance: assessing competing perspectives - Thomas, Kyle J. (Criminology, 2023)
Laub and Sampson (2003) and Paternoster and Bushway (2009) offered opposing explanations of desistance from crime. Yet, extant research has failed to test the key theoretical differences that distinguish these perspectives: 1) the temporal ordering of internal changes in identity/values and life transitions and 2) the impact of values/life transitions on offending conditional on key predictors from the opposing theory (e.g., whether marriage contributes to desistance among individuals who already hold prosocial values). We assess competing claims using data from the Pathways to Desistance. We find that within-person changes in prosocial value orientations are significantly related to within-person changes in one's likelihood of entering into serious romantic relationships and becoming employed. Conversely, life transitions are unrelated to changes in one's values. The results derived from fixed-effects Poisson models indicate high or increasing prosocial value orientations help explain offending patterns among those who enter into serious romantic relationships/get employed and help explain changes in offending among those who do not experience structural "turning points." Marriage/cohabitation is unrelated to within-person changes in offending, whereas the impact of employment has an inconsistent relationship. Theoretical and policy implications are discussed.